PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS PEMUDA, OLAHRAGA DAN PARIWISATA KABUPATEN PASER - Farida Islamiah; Harmayanto Harmayanto; Muhammad Nisfar Aminullah (Paser Institute Management and Busines, 2024)
This study aims to determine the effect of Maslow's theory of motivation (physiological needs, security needs, social needs, appreciation needs and self-actualisation needs) on employee performance at the Youth, Sports and Tourism Office in Paser Regency. Paser Regency. The sample in this study were civil servants totalling 32 people. totalling 32 people. The data collection tool is a questionnaire. The data collected then analysed using multiple linear regression. The results The results showed that physiological needs, social needs and self self-actualisation needs have a significant effect on employee performance at the Youth, Sports and Tourism Office in Paser Regency. While the need for security needs and appreciation needs have no significant effect on employee performance at the Youth, Sports and Tourism Office in Paser Regency. Translated with DeepL.com (free version)